Carbonic anhydrase XII in valve interstitial cells promotes the regression of calcific aortic valve stenosis. (May 2015) - Bouchareb, Rihab; Côté, Nancy; Marie-Chloé-Boulanger,; Le Quang, Khai; El Husseini, Diala; Asselin, Jérémie; Hadji, Fayez; Lachance, Dominic; Shayhidin, Elnur Elyar; Mahmut, Ablajan; Pibarot, Philippe; Bossé, Yohan; et al.
Abstract: Aims: Calcific aortic valve stenosis (CAVS) is the most common heart valve disease. In the present work we sought to determine the reversibility of mineralization in the aortic valve. Methods and results: By using in vitro analyses we found that valve interstitial cells (VICs) have the ability to resorb minerals. We documented that agonist of P2Y2 receptor (P2Y2R) promoted the expression of carbonic anhydrase XII (CAXII) at the cell membrane of VICs, whereby minerals are resorbed. P2Y2R-mediated mineral resorption was corroborated by using mouse VICs isolated from wild type and P2Y2R −/− mice. Measurements of extracellular pH (pHe) by using core–shell nanosensors revealed that P2Y2R-mediated CAXII export to the cell membrane led to an acidification of extracellular space, whereby minerals are resorbed. In vivo, we next treated LDLR −/− /ApoB 100/100 /IGF2 mice, which had developed CAVS under a high-fat/high-sucrose diet for 8 months, with 2-thioUTP (a P2Y2R agonist) or saline for the next 2 months. The administration of 2-thioUTP (2 mg/kg/day i.p.) reduced the mineral volume in the aortic valve measured with serial microCT analyses, which improved hemodynamics and reduced left ventricular hypertrophy (LVH). Examination of leaflets at necropsy confirmed a lower level of mineralization and fibrosis along with higher levels of CAXII in mice under 2-thioUTP. In another series of experiment, the administration of acetazolamide (a CA inhibitor) prevented the acidification of leaflets and the regression of CAVS induced by 2-thioUTP in LDLR −/− /ApoB 100/100 /IGF2 mice. Conclusion: P2Y2R-mediated expression of CAXII by VICs acidifies the extracellular space and promotes the regression of CAVS. Highlights: P2Y2 receptor (P2Y2R) promotes the expression of carbonic anhydrase CAXII. Overexpression of CAXII promotes the acidification of the extracellular space. The extracellular acidification of VICs promotes the resorption of minerals. Agonist of P2Y2R promoted the regression of aortic stenosis.